2014
DOI: 10.1007/s13762-014-0617-9
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and equilibrium study of Ni(II) sorption from aqueous solutions onto Peganum harmala-L

Abstract: In this study, the adsorption behavior of Ni(II) in an aqueous solution system using natural adsorbent Peganum harmala-L was measured via batch mode. The prepared sorbent was characterized by scanning electron microscope, Fourier transform infrared spectroscopy, N 2 adsorptiondesorption and pH zpc . Adsorption experiments were carried out by varying several conditions such as contact time, metal ion concentration and pH to assess kinetic and equilibrium parameters. The equilibrium data were analyzed based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 41 publications
1
24
0
2
Order By: Relevance
“…The results show that the activated carbon has a large adsorption capacity for the removal of the investigated metals in a relatively short period of time, which is consistent with other studies that have investigated the adsorption of ions on alternative adsorbents (Li et al, 2010;Ghasemi et al, 2014a;Coelho et al, 2014). Based on these results it can be observed that the adsorption of metal ions occurs in two phases.…”
Section: Effect Of Contact Timesupporting
confidence: 90%
“…The results show that the activated carbon has a large adsorption capacity for the removal of the investigated metals in a relatively short period of time, which is consistent with other studies that have investigated the adsorption of ions on alternative adsorbents (Li et al, 2010;Ghasemi et al, 2014a;Coelho et al, 2014). Based on these results it can be observed that the adsorption of metal ions occurs in two phases.…”
Section: Effect Of Contact Timesupporting
confidence: 90%
“…5b) did not give a straight line passing through the origin, indicating that intraparticle diffusion was not the only rate determining step. The graph shows three portions: the initial linear portion due to the rapid external surface adsorption of solute on available binding sites of the sorbent; the next linear part due to gradual adsorption where intraparticle diffusion is the rate controlling step; and in the third part, due to very low adsorbate concentrations in the solution, the intraparticle diffusion starts to slow down leading to equilibrium as shown by the plateau region (Ghasemi et al 2014). ?…”
Section: Kinetic Studymentioning
confidence: 99%
“…A large volume of work on the adsorption of heavy metal ions from mono-metal solutions by various adsorbents is available in literatures (Vinh et al 2015;Reddy et al 2015;Ghasemi et al 2014;Mahajan and Sud 2013;Machida et al 2006;Kadirvelu et al 2004;Li et al 2003;Nguyen et al 2013). Multi-metal adsorption studies are important to assess the level of interference caused by coions present in the wastewater and the efficiency of adsorbent to remove those ions from wastewaters (Srivastva et al 2006).…”
Section: Introductionmentioning
confidence: 99%